Dynamics of post fire plant community assembly in Doñana coastal dunes - Sergio Chozas; André F. Mira; Manuel Serrano; Nagore G. Medina; Joaquín Hortal; María Cruz Díaz-Barradas (Scientific Reports)
Abstract Fire significantly contributes to the distribution, composition, and functioning of ecosystems. It is also among the most damaging disturbances, exacerbated by increasing fire intensity and extent due to climate change. However, some ecosystems, like Mediterranean scrublands, recover quickly due to species’ adaptations to frequent fire regimes. This study investigates the community assembly processes during a secondary succession following the fire in a dune system within Doñana Natural Park, Southern Spain. To achieve this, three shrub communities were characterised along a coast-to-inland gradient over two consecutive years using a Non-Metric Multidimensional Scaling ordination. Then, a set of ecophysiological and structural traits of the dominant shrub species were analysed through a Principal Component Analysis, and correlation analyses were performed to assess the relationships between the three communities and the studied traits. Finally, to investigate the spatial structure of the shrub communities, a co-occurrence network was constructed and Moran’s I analyses were conducted. The results revealed that natural secondary succession has restored shrub communities along the gradient to states similar to those existing before the fire, indicating a consistent recovery pattern. Although species composition was comparable across zones, community spatial structure and several traits varied from coastal to interior areas, with more complex co-occurrence networks observed inland. Overall, the results underline the significance of environmental filters and species interactions in shaping community assembly during secondary succession after fire. Furthermore, they highlight that post fire community responses can be predicted through mechanisms linking the regional species pool, regeneration traits, and physical heterogeneity.